Risk Factors For Coronary Heart Disease At Mukomuko Regional General Hospital, Bengkulu Province - Risana, Dyah; Wulandari, Wulandari; Darmawansyah, Darmawansyah (Universitas Dehasen Bengkulu, 2023)
Coronary heart disease causes 15% mortality in the world. In Indonesia, 220,372 people died during 2022 due to heart disease. CHD cases at Muko-Muko Hospital in 2021 were 56 and experienced an increase in 2022 of 62 cases. CHD death cases in 2021 were 8 cases, and there was an increase in 2022 of 18 cases. The purpose of the study was to find out the risk factors associated with the incidence of coronary heart disease at the Regional General Hospital of Muko-Muko Regency. This study uses quantitative methods with a Case Control Study approach and sampling techniques using consecutive sampling techniques with a total sample of 62 cases and 62 controls. Instruments in this study used questionnaires and observation sheets. The research analysis used univariate and bivariate analysis with the chi square test. The results showed that most of the respondents had an age ≥ 40 years by 52.4%, most of the respondents had secondary education by 50.0%, most of the respondents had a history of hypertension by 55.6%, some of the respondents smoked ≥ 12 cigarettes per day by 58.1%. The results of bivariate analysis of age (p = 0.000; OR = 11.9), history of hypertension (p = 0.000; OR = 9.4), smoking habits (p = 0.000; OR = 16.5), and stress (p = 0.000; OR = 17.1) are significantly related to the incidence of coronary heart disease in Kaur Regional General Hospital. It is recommended that there is a need for increased health promotion by health workers in the community about improving the quality of life through healthy living behaviour and avoiding risk factors for CHD.